Comprehensive phytochemical profiling of American ginseng in Jilin province of China based on ultrahigh‐performance liquid chromatography quadrupole time‐of‐flight mass spectrometry. (1st November 2021) - Jiao, Yufeng; Si, Yu; Li, Le; Wang, Cuizhu; Lin, Hongqiang; Liu, Junli; Liu, Yunhe; Liu, Jinping; Li, Pingya; Li, Zhuo
Abstract: American ginseng (AG), the underground part of Panax quinquefolium L., is composed of four morphological regions, including main root (MR), lateral root (LR), fibrous root (FR), and rhizome (RH). In the clinical, MR is the main medicinal region, other regions are rarely attention. Aiming at revealing the chemical composition of AG and making better use of AG, screening analysis and metabolomic analysis were both performed to profile MR, LR, FR, and RH. First, in the systematical screening analysis, a total of 134 compounds (including 122 shared components) with various structural patterns were identified and tentatively characterized. The results indicated that the phytochemicals with various structural types were rich in MR, LR, FR, and RH. Second, 6, 4, 8, and 11 chemical markers were identified from MR, LR, FR, and RH, respectively. Seven triterpene saponins (protopanaxatriol, quinquenoside R1, ginsenoside Rc, Rk1, Rg1, Re, and vinaginsenoside R1 ) might be used for rapid differentiation of four morphological regions. This comprehensive profile study of metabolites illustrated the similarities and differences of phytochemicals in four morphological regions of AG. The results could be used for the quality control of AG and furnish a basis for the further development and utilization of AG sources.